A fictional commons: Natsume Sōseki & the properties of modern literature - Bourdaghs, Michael K. (Duke University Press, 2021)
Introduction: Owning up to Sōseki -- Fables of property : nameless cats, stray sheep, trickster badgers -- House under a shadow : disowning the psychology of possessive individualism in the gate -- Property and sociological knowledge : Sōseki and the gift of narrative -- The tragedy of the market : women, younger brothers, and colonial subjects in Kokoro -- Epilogue: Who owns Sōseki? Or, how not to belong to world literature.